A Behavioral and Event-Related Potentials Study of Food-Related Inhibitory Control in Probable Binge Eating Disorder - Yan WS; Liu MM; Liu SJ (Psychology Research and Behavior Management, 2023)
Wan-Sen Yan,1,2 Meng-Meng Liu,1 Su-Jiao Liu1 1Department of Psychology, School of Medical Humanitarians, Guizhou Medical University, Guiyang, People’s Republic of China; 2Guizhou Research Institute for Health Development, Guizhou Medical University, Guiyang, People’s Republic of ChinaCorrespondence: Wan-Sen Yan, Department of Psychology, School of Medical Humanitarians, Guizhou Medical University, 9 Beijing Road, Yunyan District, Guiyang, 550004, People’s Republic of China, Tel +86-136-4850-4644, Email yanwansen@163.comBackground: Similar to addictive disorders, deficits on cognitive control might be involved in the onset and development of Binge Eating Disorder (BED). However, it remains unclear whether general or food-related inhibitory control impairments would be basically linked to overeating and binge eating behaviors. This study thus aimed to investigate behavioral performance and electrophysiological correlates of food-related inhibitory control among individuals with binge eating behavior.Methods: Sixty individuals with probable BED (pBED) and 60 well-matched healthy controls (HCs) were assessed using the typical Stop-Signal Task, a revised Go/No Go Task, and a food-related Go/No Go Task. Besides, another separate sample, including 35 individuals with pBED and 35 HCs, completed the food-related Go/No Go Task when EEG signals were recorded with the event-related potentials (ERPs).Results: The data revealed that the pBED group performed worse with a longer SSRT on the Stop-Signal Task compared with HCs (Cohen’s d = 0.58, p = 0.002). Moreover, on the food-related Go/No Go Task, the pBED group had a lower success rate of inhibition in no-go trials (Cohen’s d = 0.47, p = 0.012). The ERPs data showed that in comparison with HCs, the pBED group exhibited increased P300 latency (FC1, FC2, F3, F4, FZ) in the no-go trials of the food-related Go/No Go Task (Cohen’s d 0.56– 0.73, all p < 0.05).Conclusion: These findings suggested that individuals with binge eating could be impaired in both non-specific and food-related inhibitory control aspects, and the impairments in food-related inhibitory control might be linked to P300 abnormalities, implying a behavioral-neurobiological dysfunction mechanism implicated in BED.Keywords: binge eating disorder, inhibitory control, stop-signal, Go-No Go, ERPs